2019
DOI: 10.1097/prs.0000000000005320
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Online Plastic Surgeon Reviews for Abdominoplasty

Abstract: Background: Online reviews increasingly influence patients’ decision-making. This is the first systematic, quantitative analysis of online reviews for abdominoplasty. Methods: Reviews for abdominoplasty were sampled from RealSelf, Yelp, and Google for six major metropolitan areas. A standard social sciences framework known as grounded theory was used to evaluate factors affecting satisfaction. The relative importance of factors was quantified using odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Although there is hesitation about online reviews as they may undermine a surgeon's expertise, 21 our study found overwhelmingly positive results. These results were not only found in breast reconstruction, but also for abdominoplasty, 22 blepharoplasty, 23 and rhytidectomy. 24 However, this information differs from available BREAST-Q data as one study demonstrated that women are on average satisfied 78.2% compared with our finding of 94.33%.…”
Section: Takeawaysmentioning
confidence: 66%
“…Although there is hesitation about online reviews as they may undermine a surgeon's expertise, 21 our study found overwhelmingly positive results. These results were not only found in breast reconstruction, but also for abdominoplasty, 22 blepharoplasty, 23 and rhytidectomy. 24 However, this information differs from available BREAST-Q data as one study demonstrated that women are on average satisfied 78.2% compared with our finding of 94.33%.…”
Section: Takeawaysmentioning
confidence: 66%
“…Similar to the aesthetic surgery market, we find that women are still influenced by online reviews and reputation when selecting a breast reconstruction surgeon. Online reviews and advertising in plastic surgery have been shown to be influenced by outcomes unrelated to surgical outcome, including interactions with other staff and cost, 39 with many reviews written by those who were seen in consult for but did not undergo surgery. 40 Although many of these reviews are nonmodifiable, our study suggests that even academic breast reconstruction surgeons should be aware of their online presence and profile in terms of how it translates to rapport with potential patients.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that aesthetic outcome is a major predictor of patient satisfaction after abdominoplasty, further underlying the need to develop a robust aesthetic scale. 15 We aimed to build on Salles and colleagues' work by integrating layperson perceptions of abdominal aesthetics into the design of a professional aesthetic scale for the abdomen. In this article, we describe the development and initial validation of the scale, which uses crowdsourced, layperson opinions on abdomen aesthetics to weight scale items.…”
Section: Ementioning
confidence: 99%
“…Research suggests that aesthetic outcome is a major predictor of patient satisfaction after abdominoplasty, further underlying the need to develop a robust aesthetic scale. 15…”
mentioning
confidence: 99%